2017
DOI: 10.1016/j.scr.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A Marfan syndrome human induced pluripotent stem cell line with a heterozygous FBN1 c.4082G > A mutation, ISMMSi002-B, for disease modeling

Abstract: Fibroblasts of a 28-year-old female with Marfan syndrome (MFS) due to a heterozygous FBN1 c.4082G>A mutation were reprogrammed using the Sendai virus delivery method. The established human induced pluripotent stem cell (hiPSC) line named ISMMSi002-B expresses pluripotency markers, has a normal karyotype, carries the specific FBN1 mutation and is able to differentiate into three germ layers in vitro. ISMMSi002-B has utility in studying MFS pathogenesis, including skeletal abnormalities, cardiomyopathy, and vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…qRT-PCR was performed on an ABI7500 PCR machine using the SYBR Green PCR Master Mix (Toyobo Co. Ltd., Osaka, Japan). The primer sequences are shown in Table 1 [14, 15, 16, 17, 18, 19, 20, 21, 22]. Expression differences were calculated by the 2-ΔΔCt method [23].…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was performed on an ABI7500 PCR machine using the SYBR Green PCR Master Mix (Toyobo Co. Ltd., Osaka, Japan). The primer sequences are shown in Table 1 [14, 15, 16, 17, 18, 19, 20, 21, 22]. Expression differences were calculated by the 2-ΔΔCt method [23].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, evidence that reprogrammed cells can be differentiated into osteoblasts [ 54 , 55 , 56 ], chondrocytes [ 57 , 58 , 59 , 60 ], myoblasts [ 61 ], nucleus pulposus cells [ 47 , 48 , 49 ] and tenocytes [ 62 ] has recently impacted musculoskeletal research and changed orthopedic medicine. Nevertheless, the use of iPSCs for studying the wide variety of musculoskeletal conditions has been explored to a limited extent ( Table 1 ) in comparison with conditions affecting nervous or cardiac pathologies, even when investigating genetic disorders where symptoms affect several organs or systems [ 63 , 64 , 65 , 66 ].…”
Section: Disease Modelingmentioning
confidence: 99%
“…MFS is an autosomal dominant genetic disorder of the connective tissue caused by mutations in the FIBRILLIN-1 (FBN1) gene and associated with skeletal deformities (disproportionate growth, scoliosis), among other symptoms [ 63 , 64 , 65 ]. Klein et al [ 63 ] reprogrammed skin fibroblasts derived from an MFS patient and demonstrated the presence of a mutation in the FBN1 gene in the established iPSC line by sequencing. Park et al [ 64 ] went a step further and derived iPSCs from an MFS patient with an FBN1 mutation and corrected it, thereby generating isogenic “gain-of-function” control cells for the parental MFS-iPSCs.…”
Section: Disease Modelingmentioning
confidence: 99%
“…12 In vitro MFS patient-specific cell models have served as an effective tool in multiple studies of pathogenesis, drug screening, and gene-editing therapy. [33][34][35] Recent studies also utilized iPSC-derived aortic cells to investigate the pathogenesis of MFS aortopathy.…”
Section: Coculturing Of Cells To Model Cellular Crosstalkmentioning
confidence: 99%